The effects of chiropractic adjustment on inattention, hyperactivity, and impulsivity in children with attention deficit hyperactivity disorder: a pilot RCT - Amjad, Imran; Niazi, Imran Khan; Kumari, Nitika; Duehr, Jens; Shehzad, Gulyana; Rashid, Usman; Duehr, Jenna; Trager, Robert J.; Holt, Kelly; Haavik, Heidi (Frontiers in Psychology, 2024)
Background Attention deficit hyperactivity disorder (ADHD) is a neurobiological disorder characterized by inattention, hyperactivity, and impulsivity. We hypothesized that chiropractic adjustments could improve these symptoms by enhancing prefrontal cortex function. This pilot study aimed to explore the feasibility and efficacy of 4 weeks of chiropractic adjustment on inattention, hyperactivity, and impulsivity in children with ADHD. Methods 67 children with ADHD were randomly allocated to receive either chiropractic adjustments plus usual care (Chiro+UC) or sham chiropractic plus usual care (Sham+UC). The Vanderbilt ADHD Diagnostic Teacher Rating Scale (VADTRS), Swanson, Nolan and Pelham Teacher and Parents Rating Scale (SNAP-IV), and ADHD Rating Scale-IV were used to assess outcomes at baseline, 4 weeks, and 8 weeks. Feasibility measures such as recruitment, retention, blinding, safety, and adherence were recorded. Linear mixed regression models were used for data analysis. Results 56 participants (mean age ± SD: 10.70 ± 3.93 years) were included in the analysis. Both the Chiro+UC and Sham+UC groups showed significant improvements in total and subscale ADHD scores at 4 weeks and 8 weeks. However, there were no significant differences between the two groups. Conclusion This pilot study demonstrated that it was feasible to examine the effects of chiropractic adjustment when added to usual care on ADHD outcomes in children. While both groups showed improvements, the lack of significant between-group differences requires caution in interpretation due to the small sample size. Further research with larger samples and longer follow-up periods is needed to conclusively evaluate the effects of chiropractic adjustments on ADHD in children.